An investigation of fetal behavioural states during maternal sleep in healthy late gestation pregnancy: an observational study. (2nd November 2017) - Stone, Peter R.; Burgess, Wendy; McIntyre, Jordan; Gunn, Alistair J.; Lear, Christopher A.; Bennet, Laura; Mitchell, Edwin A; Thompson, John M. D.; ,
Abstract : Key points: Fetal behavioural state in healthy late gestation pregnancy is significantly affected by maternal position overnight. Maternal left lateral position is the one most frequently adopted at sleep onset. The maternal position at sleep onset is maintained the longest overnight. Fetal state 1F is more common in maternal supine positions overnight. Fetal state 4F is less common in maternal supine sleep positions. Fetal state and maternal sleep position are independently associated with fetal heart rate variability. Maternal sleep position significantly affects fetal heart rate and heart rate variability and affects circadian fetal heart rate patterns. Abstract: Fetal behavioural states (FBS) are measures of fetal wellbeing. Maternal position affects FBS with supine position being associated with an increased likelihood of fetal quiescence consistent with the human fetus adapting to a lower oxygen consuming state. Several studies have now confirmed the association between sleep position and risk of late intrauterine death. We designed this study to observe the effects of maternal sleep positions overnight in healthy late gestation pregnancy. Twenty‐nine healthy women had continuous fetal ECG recordings overnight. Two blinded observers assigned fetal states in 5 min blocks. Measures of fetal heart rate variability (FHRV) were calculated from ECG beat to beat data. Maternal position was determined from infrared video recording. Compared to state 2F (active sleep), 4F (active awake‐high activity) occurred almost exclusively when the mother was in a left or right lateral position. State 1F (quiet sleep) was more common when the mother was supine [odds ratio (OR) 1.30, 95% confidence interval (CI) 1.11–1.52] and less common on the maternal right side with the left being the referent position (OR 0.81, 95% CI, 0.70–0.93). State 4F was more common between 21.00 and 01.00 h than between 01.00 and 07.00 h (OR 2.83, 95% CI 2.32–3.47). In each fetal state, maternal position had significant effects on fetal heart rate and measures of FHRV. In healthy late gestation pregnancy, maternal sleep position affects FBS and heart rate variability. These effects are probably fetal adaptations to positions which may produce a mild hypoxic stress. Key points: Fetal behavioural state in healthy late gestation pregnancy is significantly affected by maternal position overnight. Maternal left lateral position is the one most frequently adopted at sleep onset. The maternal position at sleep onset is maintained the longest overnight. Fetal state 1F is more common in maternal supine positions overnight. Fetal state 4F is less common in maternal supine sleep positions. Fetal state and maternal sleep position are independently associated with fetal heart rate variability. Maternal sleep position significantly affects fetal heart rate and heart rate variability and affects circadian fetal heart rate patterns.